Mampukah Good Corporate Governance dan Risiko Kredit Sebagai Prediktor Financial Distress? - Elysa Listiana Putri; Sugeng Haryanto; Riril Mardiana Firdaus (AFRE (Accounting and Financial Review), 2018)
This study aims to predict financial distress at Bank foreign exchange (BUSN) by using GCG analysis, credit risk, profitability, capital adequacy ratio and bank size. GCG, credit risk, and profitability. The population in this research is 35 BUSN of foreign exchange registered in Bank Indonesia. Sampling technique used purposive sampling. The sample size is 17 banks. Data analysis technique using linear regression. This research performs 4 regression test that is in BUSN of foreign exchange for all condition, financial distress condition, grey area condition, and condition of non-financial distress. The results of this study indicate that GCG and credit risk have no effect on financial pressure for all conditions, financial distress condition, grey area condition, and non-financial distress condition. Profitability affects financial difficulties for all conditions, grey area conditions and non-financial distress conditions. CAR affects financial difficulties for all conditions, grey area conditions and non-financial pressure conditions. Profitability and CAR have no effect on financial difficulties for grey area conditions. The size of the bank affects financial difficulties in all conditions and greys, whereas in the financial distress position the size of the bank does not affect financial distress. DOI:  https://doi.org/10.26905/afr.v1i1.2291